Pandangan Islam tentang Kedudukan HAM bagi Non-Muslim: Pendekatan Fiqh Politik - Akhmad Muzakki (el Harakah: Jurnal Budaya Islam, 2000)
The concept of human rights is the result of cultural ingredients that are not based on the principle of religion, so it is anthropocentric, that is focused only on the human itself. Even in the secular West's view, human rights are the expression of human freedom irrespective of God's provisions, religion, morals or metaphysical obligations. In contrast to the Islamic view, that human rights and even human beings are God's grace and will come back later. Based on this, human rights in Islam are theocentric, that is aimed at and sourced from God. Islam places human rights as a consequence of the obligation to God. Externally, the Islamic state is totally separate from other non-Islamic communities. Internally, the Islamic state is an ummah and a group of people united with one another by the ties of Islamic (Islamic) equality. States can not impose restrictive measures and diminish their rights altogether. Konsep HAM adalah hasil ramuan budaya yang tidak berpijak pada prinsip agama, maka ia bersifat antroposentris, yakni terfokus hanya pada manusia itu sendiri. Bahkan dalam pandangan Barat sekuler, HAM adalah ekspresi kebebasan manusia yang terlepas dari ketentuan Tuhan, agama, moral atau kewajiban metafisika. Berbeda dengan pandangan Islam, bahwa HAM bahkan wujud manusia sekalipun adalah anugerah Tuhan dan kepada-Nya kelak akan kembali. Berdasarkan ini, HAM dalam Islam bersifat teosentris, yakni bertujuan untuk dan bersumber dari Tuhan. Islam menempatkan HAM sebagai kosekuensi dari pelaksanaan kewajiban terhadap Allah. Secara eksternal, negara Islam sama sekali terpisah dari komunitas lain bukan Islam. Secara internal, negara Islam adalah suatu ummah dan sekumpulan orang-orang yang dipersatukan antara satu dengan yang lain oleh ikatan persamaan agama { Islam ). Negara tidak dapat mengadakan tindakan pembatasan dan pengurangan hak-hak mereka walau sedikitpun.